The Development of Polyclonal Antibody Against Glucose-6-Phosphate Dehydrogenase (G6PD) for G6PD Deficiency Newborn Screening in Indonesia - Fauziah, Dina; Wijaya, Andreas Budi; Loverita, Dyta; Aulanni’am , Aulanni’am; Wuragil , Dyah Kinasih; Khairana , Almas Dwi; Putra, Alvino Ramadhany; My Wulan, Nada Balqis; Nilasari , Karina (Scripta Medica, 2026)
Background/Aim: Glucose-6-phosphate dehydrogenase (G6PD) deficiency, an enzymatic disorder affecting carbohydrate metabolism, is a common cause of haemolytic anaemia and jaundice in newborns. Despite the proven benefits of G6PD screening, Indonesia faces significant challenges in implementing nationwide programs. Standard screening via dried blood spot (DBS) samples has limitations, prompting the need for improved diagnostic methods. This study aimed to develop a more sensitive and accessible screening method by creating polyclonal antibodies against G6PD. Methods: G6PD protein was isolated from newborn cord blood and confirmed using western blot analysis. The rabbits were immunised with purified G6PD antigen. The polyclonal antibody with the highest titre was purified by SAS method. Results: Western blotting confirmed the presence of G6PD at approximately 56 kDa in the isolated protein fraction. Immunised rabbits showed a significant increase in antibody titre compared with the control group. This research successfully isolated G6PD and produced polyclonal antibodies against it. However, further work is required to fully characterise the antibody and evaluate its suitability for G6PD deficiency screening. This antibody development holds promise for creating a dipstick kit for G6PD deficiency screening, thus overcoming the limitations of the DBS method. Colloidal gold-based immunochromatographic strips could be a suitable platform for such a kit due to their ease of use and rapid results. Conclusion: Presented findings constitute a solid foundation for introducing a novel immunochemical reagent and developing a rapidly scalable protocol for producing G6PD-specific antibodies.